Hemorrhage and complication after dental extraction on patients receiving Warfarin Potassium (WP) ; A study by the five WP controlled procedures - Miyako, Haruhiko; Kikuta, Toshihiro; Okushima, Yasuko (Journal of Japanese Society of Dentistry for Medically Compromised Patient, 2003)
There is no secure manual for dental extraction without local hemorrhage and general complication on patients receiving Warfarin Potassium (WP). We studied the hemorrhage and complication retrospectively after dental extraction by the five WP controlled procedures in our department of Fukuoka University Hospital for 7 years and 4 months from January 1, 1996 to April 30, 2003. Subjects were 74 patients receiving WP (Maintained group: 16, Reduced group: 11, Reduced and suspended group: 4, Suspended group: 35, Heparinized group: 8). There was no case with major general complication after dental extraction. The cases with local hemorrhage after dental extraction were one in 16 on Maintained group and 3 in 35 on Suspended group. It is feasible for the patients maintained on WP therapy to have one or a few teeth extraction at a time. Heparinization is desirable procedure for dental extraction on WP receiving patients who have a data with INR of over 3, a plan of wisdom tooth extraction and a multiple teeth extractions at a time. It should be need the connecting system of hospitalization for the local hemorrhage and general complication in all day long, when the patients receiving WP therapy have the dental extraction in clinic.